Highly pathogenic avian influenza and its interface jumps between birds and mammals: current situation (Revista Sistemas de Producción Agroecológicos, 2023)
Avian influenza, caused by highly pathogenic strains of influenza A virus, has been the subject of global concern due to its ability to infect poultry and wildlife, as well as its potential for transmission to humans. This review article examines data and information provided by the Centers for Disease Control and Prevention (CDC), World Organization for Animal Health (WOAH), Department of Agriculture (USDA-APHIS), and the National Library of of Medicine (PubMed) of the United States, on avian influenza. Key aspects of the disease are addressed, including its epidemiology, transmission mechanisms, clinical manifestations, diagnosis, prevention, and control. In addition, the latest research advances are explored and future perspectives in the field of avian influenza are discussed.
Keywords: Avian influenza; Wild birds; Mutation; Pathogenicity; Zoonoses